(untitled) - Krottmaier, J. (London, 1993)
This book does not claim to be a scientific work. Instead, it aims to familiarize the reader with statistical methods for design of experiments and analysis, quickly and easily. There are a few analysis methods that cannot be statistically proven. Some of them are, however, described in this book, as they have been proved successful in pratice.
Keywords: Computer-aided design,Engineering design,Experimental design,Mathematical optimization; Data processing,Data processing